A prospective comparison of co-amoxiclav and the combination of chloramphenicol, doxycycline, and co-trimoxazole for the oral maintenance treatment of melioidosis. - Rajchanuvong, A; Chaowagul, W; Suputtamongkol, Y; Smith, MD; Dance, D; White, N (1995)
An open randomized comparison of the oral 'conventional' regimen (combination of chloramphenicol, cotrimoxazole and doxycycline) and co-amoxiclav for the maintenance treatment of melioidosis was conducted in Ubon Ratchatani, north-eastern Thailand, between 1989 and 1992. The total antibiotic treatment duration was 20 weeks. Of 101 patients followed, 10 (10%; 95% confidence interval [CI] 4.9-17.5%) subsequently relapsed: 2 of 52 patients (4%) in the oral 'conventional' group, and 8 of 49 patients (16%) receiving oral co-amoxiclav. This compares with a relapse rate of 23% in our previous study of 8 weeks' total therapy. Only 50% of patients complied with the 20 weeks' treatment regimen and poor compliance proved the most significant risk factor for subsequent relapse (relative risk [RR] 4.9, 95% CI 1.2-20.3). Neither the presence of known underlying disease nor choice of initial parenteral treatment was significantly associated with a higher risk of relapse. Co-amoxiclav is safer and better tolerated, but may be less effective (RR of relapse 0.4, 95% CI 0.2-1.2) than the oral 'conventional' regimen. The minimum duration of total treatment with either regimen should be 12-20 weeks, depending on clinical progress.